A Systematic Review of Local Wisdom-Based Learning Models in Physical Education: Effects on Physical Fitness, Social Interaction, and Enjoyment - Isra Kamar; Masrun Masrun; Aldo Naza Putra; Eval Edmizal; Wilda Welis (IICET (Indonesian Institute for Counseling, Education and Therapy), 2026)
The initial systematic search of the Scopus database using the PRISMA 2020 method found 40 records. The 10 included studies involved participants ranging from preschool to college age, were drawn predominantly from Indonesia (7 of 10 studies), with the remainder from Taiwan, Malaysia, and the Philippines, and most quasi-experimental samples comprised fewer than 100 participants; the search was deliberately confined to Scopus to ensure consistent and complete bibliographic metadata across records, a scope decision discussed further as a review limitation. This analysis whereby the selected articles show constant key points. Thirdly, bringing local wisdom into PE greatly raised elementary students' drive, pleasure, commitment, and cultural knowledge, deeply connecting learning to their lives. Eventually, playing a traditional game helped teachers not only deliver instruction but also preserve cultural heritage and strengthen the student's cultural identity. The findings indicate that local wisdom-based innovative learning models can also facilitate the emotional, physical, social development simultaneously in schools. Besides, the review points out that cultural relevance is an element that attracts students towards deeper engagement and learning. On the other hand, most of the research articles are from Southeast Asia; though, some of the sampling and quasi-experimental studies are small in number. That is why upcoming studies should look at bigger and more variable populations, incorporate instruments that can measure social-interaction and enjoyment, and compare the performance results of these approaches across different cultural settings so as to provide a stronger evidence base at the international level.